Pendidikan Islam dalam Pemikiran Hasan Langgulung - Ahmad Irfan Zebua; Intan Permata Sari Zega; Azizah Hanum OK (Jurnal Dirosah Islamiyah, 2024)
Islamic education has become an important focus in the thinking of Hasan Langgulung, a contemporary Muslim scholar who has made significant contributions to the development of Islamic thought. In his view, Islamic education is not just the transfer of religious knowledge, but a holistic process that includes spiritual, intellectual, social and moral aspects. This article reviews key concepts in Hasan Langgulung's thinking regarding Islamic education. Through critical analysis of his works, this abstract highlights the importance of Islamic education as an instrument for forming people with integrity, competence, and the ability to contribute positively to society. By understanding Hasan Langgulung's thoughts on Islamic education, we can enrich our insight in an effort to improve the education system that is more inclusive and oriented towards Islamic values. Islamic education, as a concept that combines Islamic religious values ​​with the educational process, has become the subject of significant attention in the world of education. In this context, Hasan Langgulung's thoughts are the main focus. Langgulung, a prominent Muslim intellectual, has made substantial contributions in formulating the conceptual framework and practice of holistic Islamic education. Langgulung emphasized the importance of education that not only prioritizes academic aspects, but also the formation of character who has faith and noble morals. His thoughts also highlight the need for integration between religious and general knowledge, as well as the importance of teachers as role models and mentors for students.